STRATEGI GURU KELAS 1 DALAM PENERAPAN MEMBACA PERMULAAN SEKOLAH DASAR - Mai Sri Lena; Hana Shilfia Iraqi; Zahratul Hasanah; Nelsa Maharani Putri (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
This study aims to describe the various strategies or methods used by teachers in teaching early reading in elementary schools. Qualitative research methods are used in this research. Respondents in this study are educators who teach in elementary schools with the criteria of teachers teaching in grade 1 elementary schools. In this study, data collection was carried out by distributing questionnaires to teachers who teach in grade 1 elementary schools. The results obtained in this study are as follows: Some students often forget to remember letters, so teachers have problems in teaching early reading to students, such as there are some students who have low IQ, are lazy, have low learning motivation, and also have student difficulties. to remember and understand letters. Therefore, there is a need for a strategy that must be implemented by the teacher in guiding students to learn to read at the beginning. These strategies include: syllable method, alphabetic method, SAS method, and spelling method. Each of these methods has its advantages and disadvantages. As a teacher, you must be smart in choosing the strategy to be applied whether it is suitable or not. Thus the strategy implemented by the teacher cannot be separated through collaboration between educators and parents of students, because in learning to read at the beginning it requires the role of parents.